Politics and Statecraft in the Kingdom of Greece, 1833-1843 - Petropulos, John Anthony (Princeton, NJ : Princeton University Press, 2015)
Three foreign-oriented political parties-Russian, French, and English-emerged during the Greek Revolutionary period from 1821 to 1827 and played a prominent role in Greek politics until the 1850's. Little has been known or written about the activities of these parties between 1833 and 1843, when a newly established monarchy under the Bavarian King Otho was attempting to lay the foundations of a new state. It is one of the purposes of this book to locate and classify the parties, to determine their membership, to analyze their institutional structure and societal function, and to discover why their chief identifying characteristic was their foreign orientation. The author seeks to determine the role of the parties under a nonconstitutionalist regime at a time when the basic structure of the Greek state was being created.Originally published in 1968.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface -- Contents -- Glossary -- Introduction -- Part One. Before 1833 -- I. The Setting: Bases for Political Divisions -- II. The Revolutionary Period, 1821-27: The Origins of the Parties -- III. The Kapodistrian Period (1828-31) and Interregnum (1831-32): The Crystallization of the Three Parties -- Part Two. The Royal Period of Absolutism, 1833-43 -- IV. The First Regency, February 1833-July 1834 -- V. The Armansperg Regime July 1834-February 1837 -- VI. The Early Period of Othonian Absolutism and "Russian" Ascendancy, 1837-40 -- VII. The Mavrokordatos Episode and the Near Eastern Crisis of 1839-41 -- VIII. The Later Period of Othonian Absolutism: "French" Ascendancy (1841-43) and the "Bloodless" Revolution of September 1843 -- Part Three. The Making of a Constitution -- IX. The Period of the Constituent Assembly, September 1843-March 1844 -- Conclusion -- Appendices -- Appendix I. "Memoirs concerning the philorthodox society introduced in Greece" -- Appendix II. Selected Prosopography -- Selected Bibliography -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: POLITICAL SCIENCE / General